Analisis pengaruh pajak daerah dan retribusi daerah terhadap belanja daerah dan pertumbuhan ekonomi Provinsi Jambi - Try Setyo Budi; Selamet Rahmadi; Parmadi Parmadi (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
The research objective is to see and analyze: 1). The development of regional taxes, local levies, regional spending, and economic growth as seen from the value of PDRB Jambi Province during the period 2002-2018, 2). The effect of local taxes and levies on regional spending in Jambi Province during 2002-2018 and 3). The influence of local taxes and levies on economic growth in Jambi Province during the period 2002-2018. The analysis method in this study uses quantitative and descriptive analysis methods, namely development, semi-log, and double logarithmic multiple regression analysis. The research results during the years 2002-2018, obtained: 1). The average regional tax increased by 17.03 percent, the average provincial levy increased by 16.49 percent, the average regional expenditure increased by 16.04 percent, and economic growth grew by 5.76 percent. 2). Partially (individually) or collectively, local taxes and levies have a positive and significant effect on spending on the Jambi Province at α = 5% during the period 2002-2018 and 3). Partially (individually) or collectively, local taxes and levies have a positive and significant effect on economic growth in Jambi Province at α = 5% during the period 2002-2018. Keywords: Local taxes, Regional levies, Regional expenditures, Economic growth